ENHANCING TEACHER EDUCATION THROUGH DIGITAL TECHNOLOGIES: A COMPARATIVE PERSPECTIVE FROM THE SADC REGION - Carlie Luzaan Schlebusch, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The Southern African Development Community (SADC) has prioritised the integration of learning technologies in higher education to enhance the quality of teaching and learning. This study undertakes a comparative analysis of Social Sciences teacher education at two universities, one in South Africa and one in Lesotho, to explore the prospects and prevalence of learning technologies. Framed by the Technological, Pedagogical, and Content Knowledge (TPACK) model and guided by a pragmatic qualitative case study design, the research involved student-teachers, lecturers, librarians, and educational technology specialists. Data were collected through semi-structured interviews and thematically analysed. Findings demonstrate that learning technologies fulfil diverse roles, including providing access to resources, facilitating instruction, supporting assessment, and enabling collaborative engagement. Both institutions rely on learning management systems (eThuto in South Africa and Thuto in Lesotho), complemented by e-libraries, personal devices, and social media platforms. However, their use has declined in recent years, reflecting challenges in sustaining digital integration. While substantial progress has been made, disparities in infrastructure, funding, and institutional support continue to constrain the effective adoption of these technologies. The study concludes by recommending strengthened policies, expanded digital infrastructure, and improved pedagogical strategies to enhance the preparation of future Social Sciences teachers. The findings offer insights for advancing educational technology adoption within the SADC region and provide a foundation for broader comparative studies in higher education.